Life quality after orchiectomy of the bone metastatic prostate cancer patient - Linh, Can Phuong; Lien, Bui Bich; Binh, Nguyen Thi (Tạp chí Nghiên cứu Y học, 2024)
Prostate cancer (PC) with bone metastasis has many clinical symptoms that very much affected to the patient’s quality of life (QoL). Improving cancer patient’s QoL is a mission for the health care professional workers. The study using questionaires SF-36 and UCLA-PCI-SF- a simple and common methods to evaluate the progress of orchiectomy treatment for bone metastases PC to assess the QoL and prostate-specific functions before and after orchiectomy. Clinical manifestations such as urinary tract, sexual function symptoms, anxiety, bone pain and insomnia affected the HRQoL (health related quality of life) of 53 participated patients were quite high from 69.8% up to 90.6%. After 1 month of orchiectomy, these symptoms were markedly reduced to less than 20%; Anxiety and Insomnia still affected 50.9% and 47.1% of study participant, respectively. HRQoL of 53 PC patients with bone metastasis after orchiectomy was remarkably improved. All domains of SF-36 and UCLA-PCI-SF after orchiectomy were statistically significantly increased with p-value < 0.05, except sexual bother.